2013
DOI: 10.1016/j.jpeds.2012.08.033
|View full text |Cite
|
Sign up to set email alerts
|

Massage Improves Growth Quality by Decreasing Body Fat Deposition in Male Preterm Infants

Abstract: Objectives To assess the effect of massage on weight gain and body fat deposition in preterm infants. Study design Preterm infants (29–32 wk) were randomized to Massage (n=22, 12F/10M) or Control (n=22, 12F/10M). Treatment was masked with Massage or Control administered twice-daily by licensed massage therapists (6 d/wk for 4 wk). Body weight (g), length (cm), ponderal index (PI g/cm3), body circumferences (cm), skinfold thickness (triceps TSF, mid-thigh MTSF, and subscapular SSF; mm) were measured. Circulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 29 publications
2
35
0
2
Order By: Relevance
“…In this randomized controlled trial, 36 infants with a diagnosis of GERD were assigned to a massage or a non-massage control group (Neu, Pan, Workman, Marcheggiani-Howard, Furuta, et al, 2014). Although the massaged infants received 30 minute massages twice a week for 6 weeks, they did not show a decrease in GERD symptoms.…”
Section: Full-term Newborn Massage Therapy Effects (See Table 2 For Ementioning
confidence: 99%
“…In this randomized controlled trial, 36 infants with a diagnosis of GERD were assigned to a massage or a non-massage control group (Neu, Pan, Workman, Marcheggiani-Howard, Furuta, et al, 2014). Although the massaged infants received 30 minute massages twice a week for 6 weeks, they did not show a decrease in GERD symptoms.…”
Section: Full-term Newborn Massage Therapy Effects (See Table 2 For Ementioning
confidence: 99%
“…Moyer-Mileur et al 37 used the Infant Massage USA protocol, but they modified for PI, eliminating massage of the abdomen.…”
Section: Resultsmentioning
confidence: 99%
“…Some of the studies did not assess the data statistically; part of them justified this because of small sample size. 6---8 Some correlations have been suggested to justify the faster weight gain of PI submitted to TKS, such as greater vagal stimulation and gastric activity, 28,29 relationship with energy intake, 3,10,15,17,22---31,39 sleep-wake behavior and behavioral scales, 6---8,10,14,19---27,36,39 serum insulin and IGF-1 levels, 30,37 and use of oil. 33,40,41 The results found by Diego et al 28 and Field et al 42 on the effects of mild and moderate pressure showed that moderate pressure provided greater vagal stimulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the parents notice a greater understanding of their child because they learn to identify their different types of crying and the level of urgency that requires their attention, hence, they respond better to their children's needs (4) . It also promotes the development of children through the active stimulation of the neurological system through the skin (6) , allowing for example, an early discharge in hospitalized children because of diseases due to their premature condition (7) . This latter, thanks to the stimulation of better gastric motility, that would be associated with improved digestion and absorption of food, and therefore, the stimulation of growth (8) .…”
Section: Introductionmentioning
confidence: 99%